A Review of the Triple Gains of Waste and the Way Forward for Ghana - Abalo, Emmanuel Mawuli; Peprah, Prince; Nyonyo, Julius; Ampomah-Sarpong, Rita; Agyemang-Duah, Williams (Journal of Renewable Energy, 2018)
The postcolonial waste management practices in Ghana have consistently been identified with the discarding and disposal of waste in open dumps, wetlands, and landfills. These practices have only contributed to the glaring poor sanitation in the cities of Ghana. Insignificant quantity of the waste generated ends up in recycling and/or composting units for reuse. Given the current growth of Ghana’s population, coupled with the emerging industrialisation, the country’s overdependence on hydropower for energy and natural resources for production alone is dangerous. This paper provides a holistic review of the gains from solid waste. The paper reaffirms that, through appropriate technologies, waste possesses the intrinsic potential to generate renewable energy, resources, and income. In recommending, the main objective of waste management practices in Ghana should be about exploring the economic potentials of waste. Thus, waste disposal should be the last resort, and not the first option in waste management practices in Ghana.